Techniques for Selective Labeling of Molecules and Subcellular Structures for Cryo-Electron Tomography - Kazakov, Evgeny P.; Kireev, Igor I.; Golyshev, Sergei A. (Biochemistry (Moscow), 2025)
Electron microscopy (EM) is one of the most efficient methods for studying the fine structure of cells with a resolution thousands of times higher than that of visible light microscopy. The most advanced implementation of electron microscopy in biology is EM tomography of samples stabilized by freezing without water crystallization (cryoET). By circumventing the drawbacks of chemical fixation and dehydration, this technique allows investigating cellular structures in three dimensions at the molecular level, down to resolving individual proteins and their subdomains. However, the problem of efficient identification and localization of objects of interest has not yet been solved, thus limiting the range of targets to easily recognizable or abundant subcellular components. Labeling techniques provide the only way for locating the subject of investigation in microscopic images. CryoET imposes conflicting demands on the labeling system, including the need to introduce into a living cell the particles composed of substances foreign to the cellular chemistry that have to bind to the molecule of interest without disrupting its vital functions and physiology of the cell. This review examines both established and prospective methods for selective labeling of proteins and subcellular structures aimed to enable their localization in cryoET images.